Angefleht und dann beopfert: Zur Beziehung von Mythos und Festritual in hethitischen Texten: Incited and Venerated: Thoughts on the Relation of Myth and Festival in Hittite Texts - Görke, Susanne (Journal of ancient Near Eastern religions, 2023)
This article considers the relationship of Hittite festival rituals and mythical accounts, based on the mythical narrative of the feast of the sun god, in which the invited deities are not satiated despite sufficient food and drink. It is shown that the myths of the disappearing and returning deities were originally invocations or supplications (mugawar) incorporated into ritual acts that were intended to summon a deity. From the Middle Hittite period onward, rituals for invoking deities (mukeššar) seem to have been distinguished from ritual offerings to deities, which could then be called festival rituals (EZEN₄). In the process, an occasion-bound invocation of a deity due owing to some emergency situation may have been reinterpreted as an invocation to guarantee the deity’s presence, which in the further course lost its significance for being written down while the ritual descriptions gained in importance. At the same time, the invocations may have been literarily processed and expanded, e.g., by southeast Anatolian descriptions of rites of evocation.